Determination of Capsaicin and Dihydrocapsaicin in Some Chilli Varieties using Accelerated Solvent Extraction Associated with Solid-Phase Extraction Methods and RP-HPLC-Fluorescence - Saksit Chanthai; Jureerat Juangsamoot; Chalerm Ruangviriyachai; Suchila Techawongstien (E-Journal of Chemistry)
Reversed phase-HPLC with fluorescence detection of two major capsaicinoids was described. Isocratic elution using a ratio of methanol and deionized water (66:34, v/v) as mobile phase was used at a flow rate of 0.9 mL/min with well achieved separation within 6 min. Under optimum conditions, their analytical figures of merit for the HPLC method were validated. The linearity was in the range of 1.0-25.0 μg/mL with multiple determination coefficients of higher than 0.995. The limit of detection was ranged of 0.008-0.01 μg/mL. The repeatability and reproducibility of the retention time and peak area for these compounds were in good precision with their relative standard deviations (RSDs) lower than 1% and 5%, respectively. Both capsaicin and dihydrocapsaicin were extracted using an accelerated solvent extraction (ASE) of methanol as an extraction solvent for 5 min static time with 3 cycles. The methanolic extracts were subjected to clean up with C18 solid-phase extraction (SPE) with its recoveries ranking of 90.2-98.0%. The method recoveries of real samples were found to be 60.7-98.6%. The optimized extraction method were applied for the determination of the two capsaicinoids in ten vareities of hot chilli pepper samples. Total contents of capsaicinoids were found in the range of 2,307.0-9047.3 μg/g DW with their corresponding Scoville heat unit (SHU) of 34,600-135,700. Additionally, the contents of capsaicinoids using external calibration method comparing with those of standard addition were not significantly different, indicating accuracy of the method. Mostly, the contents of capsaicin found in these real samples were rather higher than those of dihydrocapsaicin.